Hepatic Hydrothorax in Accordance with the Etiology of Cirrhosis in Patients admitted in Department of Medicine at Liaquat University of Jamshoro. - Madiha Shah, Nisar Ahmed Shah, Razia Hanif Mernon, Mahrukh Shah , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objectives: To determine the frequency of hepatic hydrothorax in accordance with the etiology of cirrhosis in patients admitted in department of medicine at Liaquat university hospital Jamshoro. Methods: This cross sectional study was conducted in the department of medicine, Liaquat University Hospital, Jamshoro. during 9th December 2014 to 8th June 2015, on 222 diagnosed cases of cirrhosis of liver fulfilling the inclusion criteria. Abdominal scan and X-ray of the chest was performed in all cases for the presence of fluid in the pleural space. Fluid analysis was performed after aspirating fluid through a intercostal approach under ultrasound guidance. All other information like age, gender, Hepatitis B or C, duration of disease, Child Pugh class and locality was recorded in proforma. The data collected was analyzed statistically and results were tabulated. Results: Hepatic hydrothorax in patients with liver cirrhosis was 6.3% (14/222), it was observed that the prevalence of cirrhosis 169(76.1%) was more pronounced among Hepatitis C patients, patients with statistically significant difference of hepatic hydrothorax in cirrhotic patients (p value < 0.0001 ).Hepatitis C virus was found the most common etiological agent responsible for cirrhosis and hepatic hydrothorax. Conclusion: Hepatic hydrothorax is a rare complication of cirrhosis. Hepatitis C virus was the commonest association responsible for cirrhosis and hepatic hydrothorax.